A Study on Pragmatic Failure in Intercultural Communication — From the Perspective of College English Teaching - Yue, Shuzhen (Journal of Educational Research and Policies, 2025)
With the deepening of globalization, intercultural communication has become an indispensable part of social life, and college English teaching, as an important channel for cultivating students’ intercultural communication competence, is facing increasingly high requirements. However, pragmatic failure in intercultural communication has always been a prominent problem in college English teaching, which seriously affects the effectiveness of students’ intercultural communication. This study, combining the author’s background in translation, experience in college English teaching, and research direction of intercultural communication and communication, takes college students as the research object to explore the types, causes of pragmatic failure in intercultural communication in college English teaching, and put forward corresponding teaching improvement strategies. Through methods such as questionnaire survey, interview and classroom observation, this study finds that the main types of pragmatic failure of college students in intercultural communication include pragmatic linguistic failure and sociopragmatic failure. The causes are mainly the lack of cultural input in college English teaching, the insufficient attention to pragmatic knowledge teaching, and the influence of students’ native language pragmatic transfer. Based on the research results, this study suggests that college English teaching should strengthen cultural input, integrate pragmatic knowledge into teaching, and carry out more intercultural communication practice activities to improve students’ intercultural pragmatic competence and reduce the occurrence of pragmatic failure.